Cicso [sic] AVVID and IP telephony design & implementation - Padjen, Robert; Walshaw, Martin (Rockland, Mass. : Syngress Pub., 2001)
Corporate demand for AVVID solutions is rapidly increasing - engineers will need this book Cisco AVVID (Architecture for Voice, Video and Integrated Data), the latest development from Cisco Systems, is redefining the way businesses communicate. AVVID allows businesses to transmit voice, data, and video over a single integrated architecture called a "multiservice" or "converged" network. Cisco AVVID Design & Implementation is designed to be a complete desk-reference for network administrators and engineers responsible for a complicated AVVID network. Covering history, protocols, hardware, servers, switches, bridges, routers, and discussions about implementation issues, realities of cost, requirements and network limitations. Engineers will learn how to design and build a comprehensive Cisco AVVID network infrastructure. Follows on from the successful Configuring Cisco AVVID Cisco engineers and other IT professionals will find this an indispensable guide when implementing AVVID Author is Systems Engineer at Cisco Unrivalled web support at solutions@syngress.com.
Keywords: Computer network architectures; Multimedia systems; Electronic books